Giant Panda - Johnson, Jinny; Illustrated by Rosewarne, Graham (London Franklin Watts, 2005)
Explains the characteristics and life cycles of familiar animals, showing how they live in the wild. Helps understanding by explaining how zoos care for these animals. Warm and simple text and outstanding illustrations throughout.
Include Index and Illustration
Keywords: Giant panda